Lived Experience of the Normal-Hearing Adolescents of Parents With Severe and Profound Hearing Impairment: A Qualitative Study With a Phenomenological Approach - Mohammad Ashori (University of Social Welfare and Rehabilitation Sciences, 2022)
Objective The current study was conducted with the aim of phenomenology of the lived experience of hearing teenagers with hearing impaired parents in Isfahan City. Materials & Methods The investigation of this research was qualitative and based on the descriptive phenomenology approach that was conducted in 2018. The participants were selected by purposive sampling among hearing teenagers with parents with severe and profound hearing loss in the schools of Isfahan, and there were ten of them. To collect data, semi-structured interviews were used and the life experiences of hearing teenagers with hearing impaired parents were investigated through interviews with them. The duration of the interviews was between 56 and 80 minutes. Results: The results of the interviews were classified into seven main categories and 38 subcategories after extracting themes. The first main category was parental acceptance, which included subcategories such as deaf parents' acceptance, willingness to communicate with parents, and parents' social acceptance. The second main category was cultural values and its subcategories included cultural differences, respect for cultures, and awareness of cultural values and beliefs. The third main category was the cycle of emotions, which included subcategories such as feelings of incompetence and weak self-efficacy in parents, emotional instability, feelings of shame and doubt, anxiety and stress, feelings of loneliness and the need for empathy. The fourth main category was social conditions, which included sub-categories such as inappropriate attitude towards deaf people, inappropriate reactions of others, social distance, poor information, inappropriate social interaction and lack of attention to social justice. The fifth main category was knowledge and thinking, whose sub-categories were parents' ignorance, hearing and deaf people's misunderstanding of each other, duality in the way hearing and deaf people think, deaf parents' lack of attention towards their children's future. The sixth main category was support networks with subcategories such as insufficient support from parents, weak support from formal and informal institutions, and lack of coordination between support sources. The last main category was life challenges, which included subcategories such as behavior management, expectations, inadequate services, financial problems, and worry about the future. Conclusion: Based on the findings, the analysis of the lived experience of hearing teenagers with hearing-impaired parents showed that they are affected by the hearing status of their parents in different ways; therefore, these categories can be used to design educational and psychological programs for hearing teenagers with hearing-impaired parents.